The Survival of the Yorùbá Healing Systems in the Modern Age - Ilesanmi Akanmidu Paul (Yoruba Studies Review, 2021)
This study investigates the philosophy and tradition of the Yorùbá healing system and the reasons for its survival into the modern age. The introduction of western-style healthcare by missionaries—which became consolidated under colonial rule, from any point of view was attempted to stiffen the survival of the former. Intentionally or inadvertently, the Yorùbá healing system was derogatorily deemed primitive and unscientific because of its ritualistic aspects, which were severely condemned. The activities of missionaries in the context of proselytism and colonial governmental policies entailed copious attempts to stifle and do away with the Yorùbá healing system. This study uses historical analysis to synchronize the factors that helped the Yorùbá healing system to survive in a threatening milieu, namely the pressures of western ideology. The study concludes that despite efforts by the propagators of western ideology, the Yorùbá healing system is still a highly favored form of healthcare in Yorùbáland.